Discipled by the West?—The Influence of the Theology of Protestant Missionaries in China on Chinese Christianity through the Translation of the Chinese Union Version of the Bible - Liu, Chao-Chun (Religions, 2021)
Over the last one hundred years, the Chinese Union Version of the Bible (CUV)—translated by Western Protestant missionaries—has enjoyed an unparalleled status as the Chinese Bible or the “Authorized Version” of the Chinese Bible. However, despite such towering significance, no scholarly works to date have systematically examined the influences of Protestant missionary theology on the translation of the CUV and, in turn, on Chinese Christianity. As an introductory attempt to explore this question, this paper first highlights this gap in current scholarship and the importance of filling this gap. Then, it presents four factors and two limitations in examining the theology of the CUV and conducts a case study on the theological topic of dichotomy versus trichotomy in the translation of the CUV along with four other Chinese Bible translations. After examining how the translators’ theology might have influenced these translations, it suggests how such influence through the translation of the CUV might have shaped Chinese Christianity both past and present, thereby demonstrating how the understanding of Chinese Christianity can be deepened by examining the relationships between missionaries’ theology, their Bible translations, and the development of Chinese Christianity.